An evaluation of the Course Experience Questionnaire in a Malaysian context for quality improvement in teaching and learning - Saputra, Eko; Handrianto, Ciptro; Pernantah, Piki Setri; Ismaniar, Ismaniar; Shidiq, Galih Albarra (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2021)
This study revealed the results of the validation of the Course Experience Questionnaire (CEQ) within the Bachelor degree students who undertook their undergraduate from a Western university with 50% of the classes conducted in Malaysia. The specific instrument has been used extensively in other contexts to investigate the teaching-learning environment in Higher Education Institutions (HEIs). A sample of 368 students from the HEIs participated in this study. The validity and reliability of the CEQ were investigated through exploratory factor analysis and Cronbach alpha coefficient. The overall course satisfaction was used as an external criterion in order to strengthen the instrument’s validity. The exploratory factor analysis identified four constructs reflecting good teaching, generic skills, appropriate assessment and clear goals and standards. The population of the research was limited and data was collected only from students of HEIs so the generalization of findings needs attention from more institutions.